Update on the management of constipation in the elderly: new treatment options - Satish SC Rao (Dove Medical Press, 2010)
Satish SC Rao, Jorge T GoSection of Neurogastroenterology, Division of Gastroenterology-Hepatology, Department of Internal Medicine, Iowa City, University of Iowa Carver College of Medicine, Iowa City, IowaAbstract: Constipation disproportionately affects older adults, with a prevalences of 50% in community-dwelling elderly and 74% in nursing-home residents. Loss of mobility, medications, underlying diseases, impaired anorectal sensation, and ignoring calls to defecate are as important as dyssynergic defecation or irritable bowel syndrome in causing constipation. Detailed medical history on medications and co-morbid problems, and meticulous digital rectal examination may help identify causes of constipation. Likewise, blood tests and colonoscopy may identify organic causes such as colon cancer. Physiological tests such as colonic transit study with radio-opaque markers or wireless motility capsule, anorectal manometry, and balloon expulsion tests can identify disorders of colonic and anorectal function. However, in the elderly, there is usually more than one mechanism, requiring an individualized but multifactorial treatment approach. The management of constipation continues to evolve. Although osmotic laxatives such as polyethylene glycol remain mainstay, several new agents that target different mechanisms appear promising such as chloride-channel activator (lubiprostone), guanylate cyclase agonist (linaclotide), 5HT4 agonist (prucalopride), and peripherally acting μ-opioid receptor antagonists (alvimopan and methylnaltrexone) for opioid-induced constipation. Biofeedback therapy is efficacious for treating dyssynergic defecation and fecal impaction with soiling. However, data on efficacy and safety of drugs in elderly are limited and urgently needed.Keywords: constipation, elderly, treatment